Etude de l'oasis traditionnelle Ghenini Gabès dans le Sud-Est de la Tunisie - Kouki, K.; Bouhaouach, H. (Tropicultura, 2009)
Study of the Traditional Oasis Chenini Gabès in the South East of Tunisia. This research was carried out in the oasis of Chenini Gabès, located in the South East of Tunisia. The objective is to characterize its physical, agronomic and socio-economic environments and to consider the advisability of installing there a composting unit to recycle waste. A field prospection and a population's investigation were carried out. Three charts were elaborated: that of the soils, the soils' occupations and the socio-economic dynamics of the populations. The point was put on the problems of salinity, bad drainage, infertility of the soils and the unbalance of the socio-economic dynamics inside the oasis. The zones North and North- East were identified as the most prosperous, the South as having the most problems of high salinity, the increased parcelling out of the exploitations, and the low profitability of the agricultural activity resulting in abandonment of farms in many cases. The soils' organic matter contents are very low (≤ 0,5%), whereas more than 5,700 tons of organic waste are lost annually by the oasis. The installation of a composting unit adapted to the context of the oasis could contribute to increase the soil fertility in the respect of a sustainable agriculture.